Quality and quantity of emission from thermal power houses / Azharudin Mukhtaruddin - Mukhtaruddin, Azharudin (1996)
Electricity has been an important energy source to people in this country. To have this energy, several ways of generation has been invented. Among them is by buming fossfl fuel. This, howevcr, gives us two different thing, energy and pollution. While energy guarenteed the continuauon of human existencc, pollution may reduced the span of human entity. The purpose of this project is to disclose the condition of pollution caused by power station. Gaussian model has been employed to estimate the concentration of pollutants emitted by the stack of the power utifittes.